2012
DOI: 10.19121/2012.report.38398
|View full text |Cite
|
Sign up to set email alerts
|

A Gender Perspective on Securing Livelihoods and Nutrition in Fish-dependent Coastal Communities

Abstract: Pe er rs sp pe ec ct ti iv ve e o on n S Se ec cu ur ri in ng g L Li iv ve el li ih ho oo od ds s a an nd d N Nu ut tr ri it ti io on n i in n F Fi is sh h-d de ep pe en nd de en nt t C Co oa as st ta al l C Co om mm mu un ni it ti ie es s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In coastal communities in Kenya, for example, fisherfolk give special access to fish to women with whom they have sex. Although such examples evince consensual trade (sexual) relationships, further examples from Zambia provides evidence that sex has been used as a coercive tool, whereby fisherfolks refuse to sell their fish to female mongers who refuse to engage in these sexual transactions (Matthews et al, 2012). Evidence from Bonny, Uganda, Kenya and Zambia reveal similarities, yet are disparate from each other, in that, fishmongers in Bonny also have to sell their bodies to non-fisherfolks for cash.…”
Section: Sex Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In coastal communities in Kenya, for example, fisherfolk give special access to fish to women with whom they have sex. Although such examples evince consensual trade (sexual) relationships, further examples from Zambia provides evidence that sex has been used as a coercive tool, whereby fisherfolks refuse to sell their fish to female mongers who refuse to engage in these sexual transactions (Matthews et al, 2012). Evidence from Bonny, Uganda, Kenya and Zambia reveal similarities, yet are disparate from each other, in that, fishmongers in Bonny also have to sell their bodies to non-fisherfolks for cash.…”
Section: Sex Workmentioning
confidence: 99%
“…Therefore, the pervasiveness of HIV in fishing communities such as those in Bonny threatens the sustainability of indigenous knowledge about fisheries resource management, as well as economic growth in the region. As Matthews et al, (Matthews et al, 2012) observed, HIV/Aids have severe economic effect as fewer fisherfolks live enough to engage in investments that will encourage growth in their communities.…”
Section: Sex Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, mama karanga is the name given to women who buy fish from fishermen, process the fish (usually through deep frying it), and sell it in their local communities or those nearby. Women report that they engage in this activity due to the lack of alternative income-earning options as the work does not require much education and skills, and although the barriers to entry are low, the profit margins are also very small (Matthews et al 2012).…”
Section: Context: Kenya and Kwalementioning
confidence: 99%
“…Additionally, failure to engage women in management efforts, coupled with women's prominent roles as environmental stewards, results in lost opportunities to improve conservation practices and sustainably manage natural resources upon which these communities' livelihoods depend. Integrating gendered considerations into conservation and development interventions increases the likelihood that they will achieve targeted outcomes of poverty alleviation and improved food security in coastal communities (Matthews et al 2012).…”
Section: Women's Inclusion and Agencymentioning
confidence: 99%